Photo-NHC Catalysis: Accessing Ketone Photochemistry with Carboxylic Acid Derivatives - Hopkinson, Matthew N.; Mavroskoufis, Andreas (Synlett, 2020)
Excitation of carbonyl groups is one of the most widely employed activation modes in photochemistry. Many synthetically important transformations, however, are successful only with aldehydes and ketones; substrates at the carboxylic acid oxidation level remain underrepresented. We have developed a conceptually novel strategy for enabling ‘ketone-like’ photochemistry with carboxylic acid derivatives that employs an N-heterocyclic carbene (NHC) organocatalyst. Using this ‘Photo-NHC’ catalysis approach, a proof-of-concept photoenolization/Diels–Alder (PEDA) reaction between acid fluorides and trifluoroacetophenones was developed. Stoichiometric studies and TD-DFT calculations supported a mechanistic scenario in which the NHC influences the absorption wavelength and inherent photochemical reactivity of the carbonyl group during the catalytic cycle.1 Introduction2 Photo-NHC Catalysis3 Conclusions
Keywords: photochemistry; N-heterocyclic carbenes; organocatalysis; photoenolization; acid fluorides; annulation; cycloaddition; carbonyls